Determinato ma possibilmente libero: la libertà del volere nella teoria psicanalitica - Guma, Francesca (Metapsychologica - rivista di psicanalisi freudiana, 2023)
This article examines the psychoanalytical theory of the freedom of will. In the context of ancient and recent debates about free will Freudian thinking has mostly been seen as a position of the denial of freedom. Naturalizing the psychic would have placed the subject on a deterministic horizon, indissolubly binding it to the laws of nature. Consistent with many of the current positions, which consider it necessary to opt for a reductionist approach to human behaviour, it has often been taken for granted that a scientific point of view of free will should be considered within a neuroscientific context. However even though certain phenomena arise out of physical events, they cannot be solely considered in physical terms. Avoiding the radical materialism, which tends to trace every single aspect of the human mind in the brain, Freudian theory is deterministic but it achieves a model of compatibility and outlines a practice able to increase free will.